Tinjauan Sistem Drainase di Jalan Perintis Kemerdekaan KM. 10 Depan Pintu 1 Unhas Kecamatan Tamalanrea - Latuheru, Alfian Feliks; Yusuf, A. Rumpang; Syahrir, Suryani (Program Studi Teknik Sipil Universitas Bosowa, 2025)
In the Tamalanrea sub-district area, when heavy rain fell on Makassar City, there were many locations where roads were flooded with water. As happened in the Perintis area, precisely on Jalan Perintis Independen (in front of door 1 Unhas), there was a puddle of water caused by the drainage channel not functioning optimally because the drainage channel was blocked and also unable to accommodate the high enough water flow. Hydrological analysis carried out Qcapacity calculations using the Manning formula and the results were compared with the requirements Qcapacity > Qplan to determine the capacity capacity of each channel section. The results of the research analysis showed that Qs = 0.529 < Qt = 0.762 for the left side drainage channel and Qs = 0.474 < Qt = 0.698 for the right side drainage channel was proven to be unable to carry the planned discharge so changes in dimensions were made to accommodate the existing discharge.